<h2>
Answer:</h2>
The equation for b is given by:
![b=2A-a](https://tex.z-dn.net/?f=b%3D2A-a)
<h2>
Step-by-step explanation:</h2>
It is given that:
A denotes the average score of the two test taken in the semester.
The two test that are taken have a score as a and b.
Now the average score A in terms of a and b is given by:
![A=\dfrac{a+b}{2}](https://tex.z-dn.net/?f=A%3D%5Cdfrac%7Ba%2Bb%7D%7B2%7D)
Now, on solving for b from this equation:
Firstly we multiply both side by 2.
i.e. we have:
![a+b=2A](https://tex.z-dn.net/?f=a%2Bb%3D2A)
Now on subtracting both side by a we have:
![b=2A-a](https://tex.z-dn.net/?f=b%3D2A-a)